Analisis Terhadap Perkawinan Beda Agama Pasca Diberlakukannya Sema Nomor 2 Tahun 2023 - Wulandari, Yossi; Nazar, Jasman (DOKTRINA: JOURNAL OF LAW, 2024)
The purpose of this study is to discuss the position of interfaith marriage according to Law Number 1 of 1974 concerning Marriage. Analysis of the circular letter SEMA Number 2 of 2023. The method used in this study is This study uses a normative research type with a statutory regulatory approach, cases and conceptual which are analyzed descriptively qualitatively. The results of the study are that the position of interfaith marriage in the Marriage Law returns to each religion and the circular issued by the Supreme Court has a major impact on society. SEMA Number 2 of 2023 is one way to end the polemic of interfaith marriage even though this interfaith marriage will continue to raise issues both in terms of population administration and in terms of Human Rights. However, with the existence of SEMA Number 2 of 2023, all judges are required to comply with these regulations and if they do not comply, the judge can be subject to sanctions by the Supreme Court Supervisory Body with various sanctions from light sanctions to heavy sanctions. Then, from a utilitarian perspective, SEMA Number 2 of 2023, these regulations lead to the degradation of the rights of citizens who will get married